What Motivates Marketing Educators to Attend In-Person and Virtual Academic Conferences in a Time of Pandemic Pedagogy?. (August 2022) - Vander Schee, Brian A.; DeLong, Debbie
The global pandemic in 2020 caused by Covid-19 required marketing educators to quickly adapt to pandemic pedagogy. It also abruptly curtailed in-person large gatherings, including academic conferences. Although many marketing scholarly professional organizations suffered a negative financial impact, the quick transition to offer completely online live events allowed many marketing educators to attend a virtual conference for the first time. After having experienced the benefits of virtual attendance, will marketing educators return to in-person attendance when it is deemed safe to do so? Marketing educators can earn credit for serving in scholarly professional organization leadership roles and for organizing and participating in academic conferences offered by those organizations. Thus, there is a vested interest in having profitable events to support the organizations. This study seeks to answer the question, what motivates marketing educators to attend in-person and virtual academic conferences? Grounded in self-determination theory, relatedness and competence are examined as marketing educator motivations. Regression analysis of the survey results suggests marketing educators have a relatedness motivation to participate in-person. They also have a competence motivation to participate virtually. Therefore, marketing scholarly professional organizations should consider offering both virtual and in-person academic conferences to address relatedness and competence motivation.